Comparative studies on trichloroethylene degradation by Fe foam catalyzing three hydrogen peroxide-based oxidants. Issue 2 (April 2022) - Huang, Jingyao; Li, Nan; Zhou, Zhengyuan; Xu, Zhiqiang; Ali, Meesam; Zeng, Guilu; Yang, Rumin; Zhou, Zhikang; Danish, Muhammad; Lyu, Shuguang
Abstract: In this paper, the effect of Fe foam (FF) (without any modification) catalyzing hydrogen peroxide (H2 O2 ), sodium percarbonate (SPC), and calcium peroxide (CP) on trichloroethylene (TCE) removal in an aqueous solution was studied for the first time. FF has good recycling and stability in oxidant/FF system for TCE removal, which was innovative and friendly to the environment with no iron leaching. Combining the SEM and EDS changes before and after FF application and the measurement results of the divalent iron, it was found that the surface of FF was destroyed and the oxygen content increased after the reaction. In addition, no dissolved iron was detected by spectrophotometry during the experiment, which revealed that the reaction basically proceeded on the catalyst surface rather than in solution. The activation effect of FF in multiple H2 O2 -based oxidant systems was investigated on the basis of adjusting the pH to 2.5. Hydroxyl radical (HO) produced in H2 O2 /FF, SPC/FF, and CP/FF systems was identified by the free radical scavenging tests, EPR spectra, H2 O2 release, and HO generation. FF owned a good recycling performance, and the removed TCE was almost completely mineralized. In the presence of surfactants, the inhibitory effect could be eliminated by increasing the dosage of the oxidant and FF. The above researches verified the effectiveness of FF activation for H2 O2 -based oxidants on TCE removal, which provided a basis for the application of oxidant/FF system in groundwater remediation of actual contaminated sites. Graphical Abstract: ga1 Highlights: Fe foam (FF) was innovatively and friendly to the environment with no iron leaching. The alkaline and neutral oxidants could be heterogeneously catalyzed by FF after adjusting the solution pH to acidic. The EPR analysis, H2 O2 release and HO generation patterns were used to compare the oxidation activity of three systems. FF without any modification has good recycling and stability.